An unstable knee with gross varus deformity treated with unconstrained total knee replacement with long tibial stem: a case report - Agrawal, Nikunj; Voonna, Charan Kumar; Sharma, Sunil; Sharma, Abhishek (International Journal of Research in Orthopaedics, 2025)
Severe varus deformity of the knee poses a technical challenge in balancing the flexion and extension gaps. Bone defects are a challenging problem encountered with severe varus deformity of knee during primary total knee arthroplasty (TKA). In this case report we have achieved good stability and alignment with unconstrained posterior stabilised TKA in unstable knee with severe varus deformity and with significant bone loss without preferring constrained options as these have concerns for longevity and difficult revision surgery. 72 years male had complaints of severe pain, swelling, deformity in both knees since 1 year and bed ridden from 6 months. History of similar complaints from past 10 years. Physical examination revealed severe varus deformity, diffuse swelling, tenderness, restricted range of movements, crepitus in bilateral knee joints. Pre anaesthetic check-up revealed patient was known coronary artery disease, on pacemaker since 7 years so anaesthetist advised to go for staged total knee replacement. Total knee replacement using unconstrained posterior stabilised implants with a long tibial stem was done, extreme varus deformity was corrected, osteophytes loose bodies removed, posteromedial tibial bone defect was repaired with cement and screw construct. It is concluded that in extreme varus deformity of the knee, if proper step-wise release is done, we can balance the knee without using constraint implants. Bone defects can be reconstructed using cement or augment. In this case, we used cement and screw construct, and the results were satisfactory. The increasing amount of evidence that supports the use of long-stem total knee replacement for complex knee osteoarthritis (OA) presentations is strengthened by this case report. While an extended period of observation is required to assess the longevity of implants.